2021
DOI: 10.1073/pnas.2026076118
|View full text |Cite|
|
Sign up to set email alerts
|

The genetic structure of the Turkish population reveals high levels of variation and admixture

Abstract: The construction of population-based variomes has contributed substantially to our understanding of the genetic basis of human inherited disease. Here, we investigated the genetic structure of Turkey from 3,362 unrelated subjects whose whole exomes (n = 2,589) or whole genomes (n = 773) were sequenced to generate a Turkish (TR) Variome that should serve to facilitate disease gene discovery in Turkey. Consistent with the history of present-day Turkey as a crossroads between Europe and Asia, we found extensive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 54 publications
2
41
0
1
Order By: Relevance
“…Our study using a rare disease model, IHH, which is not represented in the TRV patient subpopulations, confirms that TRV is well representative of the Turkish population. Kars et al ( 9 ) also reported the close genetic relationship between Balkan and Caucasian populations and those of Turkey. Previously, similar to our methods paradigm, Alkan et al ( 5 ) studied the 16 genomes from various regions of Turkey and compared them to those in the 1000 Genomes Project, and showed that the genetic structure of the people of Turkey is similar to those of Europe, particularly the Southern Europe/Mediterranean region, compared to other gene pools.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our study using a rare disease model, IHH, which is not represented in the TRV patient subpopulations, confirms that TRV is well representative of the Turkish population. Kars et al ( 9 ) also reported the close genetic relationship between Balkan and Caucasian populations and those of Turkey. Previously, similar to our methods paradigm, Alkan et al ( 5 ) studied the 16 genomes from various regions of Turkey and compared them to those in the 1000 Genomes Project, and showed that the genetic structure of the people of Turkey is similar to those of Europe, particularly the Southern Europe/Mediterranean region, compared to other gene pools.…”
Section: Discussionmentioning
confidence: 91%
“…The genetic structure of Turkish people has been investigated in small scale studies using different methods ( 5 , 6 , 7 , 8 ). In a recent study, Kars et al ( 9 ) published the first comprehensive genomic variation database, Turkish Variome (TRV), which compiles whole genome and whole exome data from 3362 individuals from various regions of Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Exome sequencing analysis was performed, including MS cases (N = 25) and unaffected family members older than 50 years of age (N = 13), revealing 42 heterozygous and 1 homozygous fully penetrant, rare or low-frequency, exonic variants (Supplementary Table S3 ). All variants were rare or low-frequency both in the gnomAD (all populations) and Turkish population based on the work by Kars et al 15 . Thirty of the heterozygous variants were located in the candidate linkage regions in family FMS01, and the homozygous variant detected in family FMS02 was located in the homozygous region with a size of 539 kb and a LOD score of 1.2 (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“… NA not available. *Variant frequencies in the Turkish population based on the work by Kars et al 15 . …”
Section: Resultsmentioning
confidence: 99%
“…The Ottoman Empire became an unprecedented mix of different ethnic and religious communities, numbering more than 25. Modern genetic research shows that a significant part of the 83.6 million population of the Republic of Turkey (in 2020) are not of Turkic origin and share a high degree of variation and admixture [40]. This means that the dynamic migration processes within the Ottoman Empire have led to significant biodiversity of different eastern (L1, L2, and L3) and western (L4) sublineages of M. tuberculosis.…”
Section: Introductionmentioning
confidence: 99%